Faktor-Faktor yang Mempengaruhi Niat Mahasiswa Akuntansi untuk Melakukan Whistleblowing - Uswatun Hasanah; Kurniawati Mutmainah (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
The purpose of this research is to determine the influence of personal costs of reporting, attitudes, subjective norms, and the level of seriousness of fraud on accounting students' intention to disclose fraud (whistleblowing) at the Al-Qur'an Science University, Central Java in Wonosobo, Accounting Study Program, Faculty of Economics and Business. The population of this study were all students of the accounting study program, Faculty of Economics and Business, Central Java Al-Qur'an Science University in Wonosobo. The sampling technique in this research was purposive sampling with certain criteria to determine the number of questionnaires distributed. Based on the purpose sampling technique used, a research population was obtained with a research sample of 95 respondents. This research method is quantitative research with primary data obtained from questionnaire data which is measured using a Likert scale. The analysis technique uses a multiple linear regression model with the SPSS program. (version 25). The results of this research prove that personal cost of reporting and attitude have no effect on accounting students' intention to disclose fraud (whistleblowing). Meanwhile, subjective norms and the level of seriousness of fraud have a positive effect on accounting students' intention to disclose fraud (whistleblowing).